Directions of Cabinet of Ministers in the course of the realization of novels legislation of Ukraine according to regulatory rent relations - Пількевич, Віталій Людвікович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article describes actual directions of Cabinet of Ministers regarding the realization of novels legislation of Ukraine in the rent relations. Author shows, that laws of Government of Ukraine and its regulations in accordance with the new standards create new integrated conditions that improve effectiveness using state property through the transfer it for rent